Perfectionism and cognitive rigidity in anorexia nervosa: Is there an association?. (10th April 2018) - Buzzichelli, Sara; Marzola, Enrica; Amianto, Federico; Fassino, Secondo; Abbate‐Daga, Giovanni
Abstract: Little is known about the relationship between neuropsychology, personality, and eating psychopathology in anorexia nervosa (AN). We aimed to investigate the interaction between set shifting and perfectionism in AN and to ascertain the role of perfectionism as a mediator between set shifting and eating psychopathology. Eighty‐five patients with AN and 71 healthy controls completed Eating Disorder Inventory‐2 (using 8 as a cut‐off for generating groups with high vs. low perfectionism), Beck Depression Inventory, Wisconsin Card Sorting Test, Trail Making Task, and Hayling Sentence Completion Task. Our findings support heightened cognitive inflexibility in individuals with AN, particularly in those with high perfectionism. Perfectionism resulted to be a mediator of the relationship between a measure of set shifting and drive for thinness, but this finding did not remain significant when including in the model only those with AN. Taken together, these data suggest a complex and nonexclusive association between set shifting, eating psychopathology, and perfectionism.